PERANAN BSPS TERHADAP EKONOMI DAN SOSIAL PENERIMA BANTUAN DI KECAMATAN SIMPANG EMPAT - KHAIRUNNISA KHAIRUNNISA; NASRUDIN NASRUDIN (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
This study aims at finding out the role of self-help housing stimulant programs for economic and social on economic and social assistance receipents in Simpang Empat Disctric. The research respondents were 42 beneficiaries with data collection techniques through questionnaires, observation and documentation. The data analysis techniques used is descriptive analysis, which is the presentation of data in tabulation form which computes the percentage for each answer category and is processed on research need which are then interpreted according to findings in the field. The result of this research of self-help housing stimulant programs are play a role in the economy by providing jobs for builders and the social conditions of beneficiaries play a roel in improving comfort and safety, health and improving housing conditions, while the economy of beneficiaries has not changed. Keywords: Self-help Housing Stimulant Assistance, Low-Income Communities, Community Welfare.